What Is Nonconsensual Sex? Young Women Identify Sources of Coerced Sex. (March 2017) - French, Bryana H.; Neville, Helen A.
Extending the American Psychological Association (APA) report on the Sexualization of Girls, this study investigated how young women identified sources of coerced sex. Findings from three focus groups with 25 Black and White adolescent women uncovered a perceived overarching force that "pushed" them to have sex before they felt ready. Participants identified four domains of coerced sex: (a) Sociocultural Context, (b) Internalized Sexual Scripts, (c) Partner Manipulation of Sexual Scripts, and (d) Developmental Status. Coerced sex was a complex system consisting of cultural, peer, and internal messages that create pressures to engage in sexual activities. Future implications for research and practice are presented.